Efforts for Legal Renewal in the Fulfillment of Women's Health Rights in Indonesia - Fitri, Selvi Relita; Redi, Ahmad (Al-Makki Publisher, 2024)
This study discusses efforts for legal renewal in fulfilling the right to public health, with a specific focus on the fulfillment of health rights for women in Indonesia. In this context, the research analyzes various existing policies and regulations, as well as the challenges faced in their implementation. The research method used is literature review, in which data is collected from various sources, including laws, government regulations, and related academic literature. The research results indicate that although there are several regulations supporting health rights for women, there are still many obstacles in accessing quality health services, including discrimination, stigma, and a lack of understanding of health rights. Legal renewal is necessary to strengthen the protection of women's health rights, including through increasing the capacity of health services, education about health rights, and strengthening the role of civil society. This article recommends the need for collaboration between the government, health institutions, and society to create an environment that supports the fulfillment of women's health rights in a comprehensive and sustainable manner.